Praehistorische Zeitschrift (De Gruyter, 1909)
The Praehistorische Zeitschrift is regarded as one of the most renowned German publications in the area of Prehistory and Ancient History. It presents detailed accounts of the most recent research conducted in Europe. The geographical emphasis is placed on Eastern, South-Eastern and Northern Central Europe. A comprehensive review section deals with recent German and international monographs from the field of prehistoric archaeology.